Immunotherapy biomarkers 2016: overcoming the barriers. Issue 1 (21st March 2017) - Gulley, James L.; Berzofsky, Jay A.; Butler, Marcus O.; Cesano, Alessandra; Fox, Bernard A.; Gnjatic, Sacha; Janetzki, Sylvia; Kalavar, Shyam; Karanikas, Vaios; Khleif, Samir N.; Kirsch, Ilan; Lee, Peter P.; et al.
Abstract : This report summarizes the symposium, 'Immunotherapy Biomarkers 2016: Overcoming the Barriers', which was held on April 1, 2016 at the National Institutes of Health in Bethesda, Maryland. The symposium, cosponsored by the Society for Immunotherapy of Cancer (SITC) and the National Cancer Institute (NCI), focused on emerging immunotherapy biomarkers, new technologies, current hurdles to further progress, and recommendations for advancing the field of biomarker development.